Research on the spatial correlation and drivers of industrial agglomeration and pollution discharge in the Yellow River Basin - Qin, Yuming; Zhang, Hao; Zhao, Huimin; Li, Di; Duan, Ye; Han, Zenglin (Frontiers in Environmental Science, 2022)
The spatial auto-correlation analysis approach is used to examine the agglomeration features and geographical correlation of industrial agglomeration and pollutant discharge using 91 prefecture-level cities in the Yellow River Basin from 2005 to 2020 as the research target. The Yellow River Basin and the upper, middle and lower reaches were investigated for the effects of industrial agglomeration on industrial pollution emissions. The Dubin model of the spatial panel is used to investigate the drivers of industrial pollution from both indirect effects and direct effects. The findings indicate that: ①The spatial pattern of industrial pollution agglomeration and agglomeration of industrial in the Yellow River Basin has spatial convergence. ②The global clustering characteristics of industrial pollution in the Yellow River Basin are apparent. The global correlations of the three pollutants are industrial wastewater> industrial smoke and dust> industrial SO2; there is a spatial association between agglomeration of industrial and pollution agglomeration, and there are differences in the spatial interconnection between agglomeration of industrial and the accumulation of different pollutants. ③From the overall point of view of the Yellow River Basin, agglomeration of industrial will reduce the pollution levels of industrial wastewater, industrial SO2, and industrial smoke and dust. From the perspective of different regions, agglomeration of industrial in the upper, middle, and lower reaches is conducive to the decline of industrial pollution, and the role is in the middle, downstream, and upstream in order from large to small. ④The Yellow River Basin's industrial pollution is primarily caused by population agglomeration, industrial structure, environmental regulation, opening to the outside world, and economic development. Their effects on industrial wastewater, industrial SO2, industrial smoke and dust pollution vary.